Educated by initiative : the effects of direct democracy on citizens and political organizations in the American states - Smith, Daniel A., 1966- (University of Michigan Press, 2004)
Educated by Initiative moves beyond previous evaluations of public policy to emphasize the educational importance of the initiative process itself. Since a majority of ballots ultimately fail or get overturned by the courts, Smith and Tolbert suggest that the educational consequences of initiative voting may be more important than the outcomes of the ballots themselves. The result is a fascinating and thoroughly-researched book about how direct democracy teaches citizens about politics, voting, civic engagement and the influence of special interests and political parties. Designed to be accessible to anyone interested in the future of American democracy, the book includes boxes (titled "What Matters") that succinctly summarize the authors' data into easily readable analyses